La igualdad de género en la universidad. Capitalismo académico y rankings globales - Reverter-Bañon, Sonia (Investigaciones Feministas, 2021)
Purpose. This article proposes to reflect on how universities are committed to gender equality. Methodology. After a theoretical reflection that introduces the current reality of universities and the framework of academic capitalism that surrounds them, I investigate the global university rankings (GURs), specifically The High Education (THE) World University Rankings. Results and Discussion. The analysis of the rankings shows us the need to rethink how, in the current reality of university practices imposed by academic capitalism, we can carry out the university equality policies that laws and regulations impose on academia. Conclusion. As a conclusion and contribution, I point out the urgency of a new conception, which puts the commitments of sustainable development and the 2030 Agenda at the center and adjusts the standards and methodologies to these objectives, and not vice versa, the objectives to the methodologies.